Professional Development of Communication And Relationship of Teacher Raudlatul Athfal's Achievement With The Community - Fu'ad Arif Noor (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
ABSTRAK. Tantangan bagi guru berprestasi dalam pengembangan profesinya menjadi guru teladan yang mampu menginspirasi bagi sesama guru. Penelitian ini dilakukan dengan tujuan untuk mengetahui bagaimana komunikasi dan hubungan guru RA berprestasi dengan masyarakat yang mampu mengembangkan profesinya. Penelitian ini menggunakan metode kualitatif dengan pendekatan psikologis yang dilakukan langsung kepada subjek yang diteliti, guna memperoleh semua data terkait komunikasi hubungan Guru RA berprestasi dengan masyarakat. Pengumpulan data menggunakan wawancara, dokumentasi, dan observasi, dengan 5 (lima) guru RA berprestasi, teknik analisis data meliputi mereduksi data, menyajikan, menarik kesimpulan dan menverifikasi. Uji keabsahan data dilakukan dengan teknik triangulasi. Penelitian berhasil mengungkap: Interaksi di dalam konteks melaksanakan tugas yang secara langsung tertuju kepada tujuan RA atau satuan pendidikan Anak Usia Dini. Interaksi di luar konteks menjalankan tugas, walaupun interaksi itu terjadi di lingkungan kerja dalam sekolah RA, serta hubungan yang baik dalam konteks melaksanakan tugas menjadi prasyarat supaya produktivitas meningkat dengan masyarakat sekitar RA. Komunikasi yang kontinu istiqomah dan proses saling memberi masukan, serta saling menerima, juga membuat koreksi diri atau instrospeksi guru beserta sekolah menjadi giat, semangat, dan kontinu. Kata Kunci: Profesi, komunikasi, Guru RA, berprestasi, masyarakat.ABSTRACT. The challenge for outstanding teachers in their professional development is to become exemplary teachers who are able to inspire fellow teachers. This research was conducted with the aim of finding out how the communication and relationship between outstanding RA teachers and people who are able to develop their profession. This study uses a qualitative method with a psychological approach that is carried out directly on the subject under study, in order to obtain all data related to the communication of the relationship between outstanding RA teachers and the community. Collecting data using interviews, documentation, and observation, with 5 (five) outstanding RA teachers, data analysis techniques include reducing data, presenting, drawing conclusions and verifying. The validity of the data was tested by using triangulation technique. The research succeeded in revealing: Interaction in the context of carrying out tasks that are directly aimed at the goals of RA or the Early Childhood Education unit. Interaction outside the context of carrying out tasks, even though the interaction occurs in the work environment within the RA school, as well as good relationships in the context of carrying out tasks are prerequisites so that productivity increases with the community around RA. Continuous communication istiqomah and the process of giving each other input, and accepting each other, also makes self-correction or introspection of teachers and schools to be active, enthusiastic, and continuous. Keyword: Profession, communication, RA teacher, achievers, society.